Inovatif Integratif Kebijakan Energi dan Ketahanan Pangan - Gaspar Pera (Publikasi Indonesia, 2022)
There are three main global challenges faced in all fields, namely complexity, change and increasing problems. A monodisciplinary approach with a single technology approach is no longer relevant to face these conditions. Innovation, integration and sustainability are the keys to face these three challenges, especially towards zero carbon emission energy that is operational. To produce bioethanol as a zero carbon emission energy source, the problem is that a large amount of thermal energy is required and a lot of